New systematically measured sand mining budget for the Mekong Delta reveals rising trends and significant volume underestimations - Gruel, Charles-Robin (2022)
The river beds of the Mekong Delta are some of the most intensively sand mined places in the world. However, sand mining budgets remain limited to rough and indirect estimates. Here, we provide a first systematic, field-based estimation of the Mekong Delta's sand mining budget. This budget overcomes the limitations of relying on officially declared statistics and bathymetric surveys of short channel reaches. We applied Sentinel-1 radar imagery to monitor the distribution of sand mining activities using boat metrics-driven mining intensity maps correlated with a field-based bathymetry difference map which were derived from two extensive bathymetric surveys conducted in 2014 and 2017. The two surveys cover ∼ 100 km in the Tiền River, reaching approximately 15% of the Mekong Delta. We then extrapolated the Tiền River findings to the broader Vietnamese Mekong Delta from 2015 to 2020 and measured a continuous increase of the extraction budget by ∼ 25% between 2015 (38 Mm3/yr) and 2020 (47 Mm3/yr). We estimated a total sand mining budget of 254 Mm3 during the 6-year study period with an average annual rate of ∼ 42 Mm3. Our field-based annual rates are higher than both official declarations provided and estimates from previous studies which implies that a substantial portion of the sand mining budget remains unaccounted for. Riverbed sand mining remains a key threat to the Mekong Delta as it contributes to a multitude of other environmental threats including dam construction effects on sedimentation, ongoing subsidence, sea level rise and recurring saltwater intrusion. This study offers a new approach that can be implemented elsewhere to allow for systematic monitoring and quantification of sand mining activities that are vital for assessing future projections on environmental impacts.